Optimizing Music Therapy for Depression Treatment: Investigating the Relationship Between Music Preferences and Mental Health - Fang, Yinyue (International Journal of Public Health and Medical Research, 2026)
Music therapy is a promising adjunct to depression care, yet effects likely vary with everyday listening. In a cross-sectional online survey (N = 736), we examined associations between preferred genres, self-reported typical tempo (beats per minute; BPM), and engagement mode (composing/playing/exploring vs. purely receptive) with single-item anxiety and depression (0–10). After prespecified cleaning (e.g., implausible BPM < 30 or > 300 excluded) and listwise analysis, we estimated OLS models with HC3 standard errors; genre differences used one-way ANOVA (inference restricted to adequately sized groups), reporting ω² and 95% CIs. Typical BPM showed small, positive linear associations with both anxiety and depression; the quadratic term was null and model R² values were modest. Genre effects were small at the omnibus level, and only a limited subset of pairwise contrasts remained significant after correction (e.g., Metal vs. Classical/R&B; Video-game music vs. Classical for anxiety). Active engagement showed selective, small associations (composition with lower depression) that warrant experimental tests. Findings, derived from a non-clinical, correlational dataset, argue for individualised use of music in practice and for prospective trials that manipulate engagement type and tempo within genres.